Percepción de la Calidad del Servicio de Agua Potable por los Habitantes del Cantón Marcabelí en el Periodo 2021. - Ríos Jarrin, Alfredo René (2024)
The objective of this curricular integration work is to carry out a diagnosis of the quality of the service provided by the Drinking Water and Sewerage Unit of the Municipal Decentralized Autonomous Government of the Marcabelí canton in order to comply with the general objective which is to "Make a diagnosis of the perception of the quality of the service of the drinking water and sewerage unit by the inhabitants of the Marcabelí canton in the period 2021" and as specific objectives "Measure the perception of users about the quality of the drinking water service through the use of the SERVQUAL method”, “Establish what are the causes and consequences which generate the failures in the quality of the drinking water service of the Marcabelí canton and propose the proposal to improve the service” in order to determine the level of user satisfaction and subsequently define proposals for improvement that meet the demands of citizens who demand to have a safe and excellent service. Accordingly, a non-experimental investigation has been carried out using the SERVQUAL method that allowed measuring the perception of users about the quality of the service through a survey made up of five dimensions that are: tangible elements; reliability; answer's capacity; safety and empathy. The survey was applied to 360 users and by means of the inductive method the relevant information has been examined, obtaining as a result the following values in each of the dimensions studied: tangible elements 2.37; reliability 0.88; responsiveness 1.50; security 0.88 and empathy 3.78 concluding that the quality of the drinking water service is moderately satisfactory for the users of the Marcabelí canton. Likewise, it was possible to detect the causes and consequences that have generated weaknesses in the quality of the service and accordingly, the proposal for improvement directed to the Drinking Water and Sewerage Unit was raised.